2017
DOI: 10.1093/ee/nvx111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Temperature on Development of Lymantria dispar asiatica and Lymantria dispar japonica (Lepidoptera: Erebidae)

Abstract: Periodic introductions of the Asian subspecies of gypsy moth, Lymantria dispar asiatica Vnukovskij and Lymantria dispar japonica Motschulsky, in North America are threatening forests and interrupting foreign trade. Although Asian gypsy moth has similar morphology to that of European and North American gypsy moth, it has several traits that make it a greater threat, the most important being the flight capability of females. Asian gypsy moth is not yet established in North America; however, infestations have bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 41 publications
2
15
0
Order By: Relevance
“…Suitable conditions for AGM were modelled in areas with annual temperatures between 5 and 25 °C, but the optimum range (probability of presence >0.60, based on maximum test sensitivity and specificity threshold 32 ) was between 11-25 °C. This optimum range is in agreement with the recent findings of Limbu et al 12 that AGM populations may struggle in regions that experience longer periods of temperatures ≥30 °C and that AGM survival was highest between 15 and 25 °C. Canadian areas classified as suitable were located within the Koppen-Geiger climatic zones-DFb (average temperatures below 22 °C) and DFc, which represents subarctic climate where 1-3 months have an average temperature above 10 °C.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Suitable conditions for AGM were modelled in areas with annual temperatures between 5 and 25 °C, but the optimum range (probability of presence >0.60, based on maximum test sensitivity and specificity threshold 32 ) was between 11-25 °C. This optimum range is in agreement with the recent findings of Limbu et al 12 that AGM populations may struggle in regions that experience longer periods of temperatures ≥30 °C and that AGM survival was highest between 15 and 25 °C. Canadian areas classified as suitable were located within the Koppen-Geiger climatic zones-DFb (average temperatures below 22 °C) and DFc, which represents subarctic climate where 1-3 months have an average temperature above 10 °C.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, gypsy moth is spreading in North America (primarily in the United States) damaging both commercial and native forest ecosystems over much of the introduced range. The pest also poses a significant economic threat to several other countries that are taking actions to prevent its introduction 12 . Two subspecies, Asian gypsy moth (L. dispar asiatica Vinkovskij), distributed throughout temperate Asia, and the Japanese gypsy moth (L. dispar japonica Motschulsky), distributed throughout Japan, are of serious concern although they have not yet permanently established (though several incursions have been eradicated) outside their native range 13,14 .…”
mentioning
confidence: 99%
“…Time to adult differed between some hosts but there was almost no significant variation between populations within a host. Female pupae from the Korean, Japanese, and Chinese populations tended to be larger, which is consistent with earlier work on these same populations [30]. Significant variation in fecundity was tied more to larval host than population, with the highest fecundity for females reared on Q. velutina and P. menziesii.…”
Section: Discussionsupporting
confidence: 87%
“…Many of these studies focused on the effects of cold temperatures, particularly shortened season lengths in colder climates, the amount of cold necessary for egg hatching and limitations on egg viability constraining northward expansion (Gray et al., 1991; Madrid & Stewart, 1981; Streifel et al., 2019). More recent work has expanded these questions to include warm temperatures (Banahene et al., 2018; Limbu et al., 2017). This area of research has shown that a range retraction along the southeastern invasion front is correlated with supraoptimal temperatures (Tobin et al., 2014) and provides support for local adaptation of fitness‐related traits in southern populations (Faske et al., 2019; Friedline et al., 2019; Thompson et al., 2017).…”
Section: Introductionmentioning
confidence: 99%